Relasi Kebiasan Belajar, Pergaulan, dan Prestasi Belajar Matematika di Lembaga Pendidikan Islam - Drajat Stiawan (Jurnal Penelitian, 2017)
This study aims to find out whether there is a positive and significant relationship between learning habits with matematics learning achievement, there is a positive and significant relationship or not between peers association with matematics learning achievement and there is a positive and significant relationship among learning habits and association of peers with matematics learning habits. The population and sampel in this research is all students of class VIII MTs Sembada Kebumen. Data accumulation technique used questionnaire and test. Data analysis used correlation analysis and regression analysis. The results show: (1) There is a positive and significant relationship between learning habits with mathematics learning achievement with correlation coefficient of 0.863; (2) There is a positive and significant relationship between peers association with mathematics learning achievement with correlation coefficient of 0.663; (3) There is a positive and significant relationship among learning habits and peers association with mathematics learning achievement with correlation coefficient of 0.874. The relative contribution of X1 is 84.39% and X2 is 15.61%. The amount of effective contribution of X1 is 64,417% and X2 is 11,91%.